The Hubungan kualitas tidur dengan premenstrual syndrome (pms) pada santriwati pondok pesantren darussalam - Haniyah, Siti (STIKES Bethesda Yakkum, 2024)
Premenstrual syndrome (PMS) is a group of symptoms in women of childbearing age due to hormonal changes related to the ovulatory cycle or the release of eggs from the ovaries. PMS appears cyclically within 7 – 10 days before menstruation begins and disappears 4 days after menstruation begins. The main factors causing PMS are hormonal factors, namely an imbalance between the hormones estrogen and progesterone, as well as changes in serotonin levels. The research aims to determine the dominant factors that influence premenstrual syndrome (PMS) in female students at the Darussalam Islamic Boarding School, Purwokerto. This research method is a descriptive research design with a cross sectional approach. The sampling technique involved a total sampling of 76 female students aged 15 – 18 years. Data was collected using questionnaires, SPAF questionnaires, PSS questionnaires, GPA questionnaires and PSQI questionnaires. The data analysis used was a logistic regression test. The results of this study show that the p value is 0.001 < 0.05, which means there is an influence between sleep quality and premenstrual syndrome (PMS) in female students at the Darussalam Islamic Boarding School with a value of (95% CI = 2,601 - 31,913), so it can be interpreted as female students with poor sleep quality. The risk of experiencing PMS is 9 times higher than that of female students who have good sleep quality after controlling for variables such as stress levels and physical activity.